2010
DOI: 10.1246/cl.2011.90
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Hybrid Liposomes Composed of Phosphatidylcholine and Docosahexaenoic Acid on the Growth of Colon Cancer Cells along with Apoptosis and Differentiation

Abstract: Novel hybrid liposomes (DMPC/DHA) composed of l-α-dimyristoylphosphatidylcholine and docosahexaenoic acid were produced. DMPC/DHA were smaller and more stable than pure DMPC liposomes. It is attractive that DMPC/DHA could remarkably inhibit the growth of human colon cancer HCT116 cells along with apoptosis and differentiation in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…It has been already reported that the diameters of DMPC/DHA composed of 10-50 mol% DHA were 60-100 nm and remained stable for 3 weeks. 19) Here, DMPC/DHA composed of 50 mol% DMPC and 50 mol% DHA were prepared by the sonication method Engineering, Sojo University; 4-22-1 Ikeda, Kumamoto 860-0082, Japan. Received December 27, 2010; accepted February 25, 2011; published online March 7, 2011 Therapeutic effects of hybrid liposomes (L-a a-dimyristoylphosphatidylcholine (DMPC)/docosahexaenoic acid (DHA)) composed of 50 mol% DMPC and 50 mol% DHA on the metastasis of human colon carcinoma (HCT116) cells were examined in vivo.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been already reported that the diameters of DMPC/DHA composed of 10-50 mol% DHA were 60-100 nm and remained stable for 3 weeks. 19) Here, DMPC/DHA composed of 50 mol% DMPC and 50 mol% DHA were prepared by the sonication method Engineering, Sojo University; 4-22-1 Ikeda, Kumamoto 860-0082, Japan. Received December 27, 2010; accepted February 25, 2011; published online March 7, 2011 Therapeutic effects of hybrid liposomes (L-a a-dimyristoylphosphatidylcholine (DMPC)/docosahexaenoic acid (DHA)) composed of 50 mol% DMPC and 50 mol% DHA on the metastasis of human colon carcinoma (HCT116) cells were examined in vivo.…”
Section: Methodsmentioning
confidence: 99%
“…It has been already reported that the diameters of DMPC/DHA composed of 10-50 mol% DHA were 60-100 nm and remained stable for 3 weeks. 19) Here, DMPC/DHA composed of 50 mol% DMPC and 50 mol% DHA were prepared by the sonication method and employed in vivo experiments. The liposomes composed of DMPC (DMPC liposomes) were prepared in the same manner as described above.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations